Re-examining provider perceptions of best pre-war practices: what elements can help opiate agonist therapy programs in Ukraine successfully survive the crisis? - Dellamura, P.; Meteliuk, A.; Fomenko, T.; Rozanova, J. (Frontiers in Public Health, 2024)
Purpose: Over the last decade, Ukraine focused on patient outcomes of expanding maintenance (OAT) programs, but providers’ experiences were overlooked. Yet, staff is the key resource of healthcare system during a crisis. Examining unique data collected in 2018 from addiction treatment providers before the Covid-19 pandemic and the subsequent Russian invasion, we reveal structural weaknesses and cultural strengths of the OAT programs that preceded the “perfect storm”. This is the first known examination of OAT providers’ perspectives in Ukraine, and it sheds light on the root causes of both the robustness and the vulnerability of OAT in Ukraine during the crisis, and its chances to endure going forward. Methodology: The data come from qualitative semi-structured interviews with 24 OAT providers throughout five regions of Ukraine. Participants included front-line nurses, addiction psychiatrists, and head doctors of Tuberculosis clinics, AIDS centers, and addiction treatment clinics that housed an OAT site. Using a coding scheme of 103 inductively developed categories we explored participants’ perceptions of their OAT program. Findings: In the stories shared by clinicians pre crisis, three major interconnected themes focused on economic uncertainty at the institutional level (leading to under-staffing), limits of structural capacity of the program, and clinicians’ professional identity, shaping application of rules for administrative discharge, take-home dosing, and efforts for scale-up. As the data were collected prior to the current crisis, findings highlight how OAT clinicians had been ‘tempered’ to overcome barriers, find creative solutions, and form a support network that became indispensable in surviving the current humanitarian catastrophe. Conclusion: the current crisis magnified pre-existing challenges as the providers’ approach toward overcoming them was already largely present before the crisis (just on a different scale). The uncertainty of resources was a constant since OAT inception in Ukraine. Historically, providers in Ukraine operated in a system that was under-funded in the absence of solid governmental funding for OAT programs, yet they came up with solutions which required ingenuity that they took pride in. This gives hope that addiction treatment in Ukraine and OAT programs will not be casualties of this humanitarian crisis and providers and their patients will persevere.